Digital narratives and citizen empowerment: Study about the perception (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
This paper shows an approximation to the actual citizen through his interaction with the digital discourses. Among the objectives, the highlights are describing the present of the empowerment’s perception, researching the interaction between the citizen and the Communicational and Informational Technologies (CIT) in different ambits, contrasting users’ perception with the experts’ perception, and getting an approximate profile able to describe the current citizen. Methodology consists of a general survey to 100 people on the one hand, and another to 12 experts on the other, to contrast these two samples’ points of view. The treated issues were general, professional, educative, informative, and leisure and entertainment. The conclusions propose a portrait of the citizen and of his empowerment through his digital interaction.
Keywords: Citizen; Empowerment; Internet; Social Networks; Digital Narratives